Influence of substituted quinones on the excretory function of the rat kidney and evaluation of the prospects of their use as potential diuretics - K.V. Sokolova; O.A. Podpletnya; S.О. Konovalova; A.P. Avdeenko; S.I. Kovalenko (Medičnì Perspektivi)
Diuretics are widely used to treat pathologies of various genesis. However, the development of side effects during their long-term use remains a problem of traditional treatment regimens. The search for diuretics that would be aimed at inhibiting a key target molecule that is involved in the regulation of salt or water balance in the kidney, and certainly have a low level of toxicity and side effects, is an urgent task for researchers. Our preliminary screening of substituted quinones using in silico and in vitro methodology identified a number of effective compounds that outperform or compete with diuretics. The compounds are not "classic" carbonic anhydrase II inhibitors, but the pronounced diuretic effect of a number of compounds requires additional explanation. Therefore, the aim of the work was to study the effect of substituted quinones on the excretory function of rat kidneys to assess the prospects of their further structural modification and use as potential diuretics. Considering the experimental data, it should be noted that compounds AVD-6, AVD-7, AVD-8 and AVD-9 have pronounced diuretic activity. Thus, according to indicators of excretory indices of electrolytes, it is possible to note the predominant influence of compounds AVD-6, AVD-7, AVD-8 and AVD-9 on excretion of sodium, potassium and chlorine from the body. Compounds AVD-6, AVD-7, AVD-8 and AVD-9, in contrast to Hydrochlorothiazide, which blocks carbonic anhydrase in the proximal part of the convoluted tubules and accelerates the excretion of potassium with from the urine, have a much lower excretory index as for these ions. Thus, our conducted research made it possible to identify a new, little-known class of hybrid molecular structures, namely (N'-(4-[(aroyloxy)imino]cyclohexa-2,5-dien-1-ylidene) aroylhydrazides (AVD-6, AVD-7, AVD-8 and AVD-9), which, in addition to affecting the excretory function of the kidneys, have significant diuretic activity and are  potential diuretics.